COMPATIBILIDADE DE METARHIZIUM ANISOPLIAE COM CARRAPATICIDAS QUÍMICOS - Soares, F.b. [UNESP]; Monteiro, A.c. [UNESP] (Instituto Biológico, 2020)
The combined use of chemical and biological control agents could prove to be a successful strategy against insects and ticks, which could improve the efficiency attained by conventional strategies and also lessen environmental impact that could be caused by these substances. The present study assessed compatibility of the entomopathogenic fungus Metarhizium anisopliae (Metsch.) Sorokin to chemical substances currently used for controlling Riphicephalus (Boophilus. microplus (Canestrini), to verify compatibility of these for possible associated use. The fungus was cultivated in a medium to which was incorporated 40, 55, 70, 85 and 100% of the recommended dosage (RD) of commercial acaricides containing various active ingredients formulated in different compositions. To verify compatibility, fungus vegetative growth, spore production and viability were assessed, and all acaricides were classified regarding toxicity. The chemical acaricides containing chlorfenvinphos + dichlorvos (Amiphós®), cipermetrin + chlorpiriphos + citronelal (Barrage®) and amitraz + chlorpiriphos (Carbeson®) were classified as toxic after causing inhibition of fungal growth and spore production, the last one being the only agent that did not affect fungal viability. The acaricide containing cipermetrin (Colosso®) was classified as compatible and moderately compatible in 40 and 65% of the RD, respectively, and the acaricide containing spinosad (Elector®) was the agent that least affected the factors evaluated, being classified as moderately compatible at 55 to 100% of the RD, and as compatible at 40% of RD. Most of the chemical acaricides evaluated were not compatible with M. anisopliae. The acaricide formulated with cipermetrin and spinosad was the only one that showed some compatibility for use in an integrated pest management.

A associação de agentes biológicos e químicos pode ser uma estratégia promissora para o controle de insetos e ácaros, visando a aumentar a eficiência, reduzir custos e impactos ambientais. Este trabalho objetivou avaliar a compatibilidade do fungo Metarhizium anisopliae (Metsch.) Sorokin com carrapaticidas químicos atualmente usados no controle de Riphicephalus (Boophilus. microplus (Canestrini). O fungo foi cultivado em meio contendo 40, 55, 70, 85 e 100% da dose recomendada (DR) de carrapaticidas comerciais contendo vários princípios ativos, formulados em diferentes composições. Avaliou-se o crescimento vegetativo, a esporulação e a viabilidade do fungo e fez-se a classificação toxicológica dos acaricidas. Os carrapaticidas contendo clorfenvinfós + diclorvós (Amiphós®), cipermetrina + clorpirifós + citronelal (Barrage®) e amitraz + clorpirifós (Carbeson®) foram classificados como tóxicos, pois inibiram o crescimento e a esporulação, e apenas o último não afetou a viabilidade do fungo. O carrapaticida contendo cipermetrina (Colosso®) foi classificado como compatível e moderadamente compatível nas doses de 40 e 65% da DR, respectivamente, e aquele contendo spinosad (Elector®) foi o que menos afetou os parâmetros avaliados, sendo moderadamente compatível nas doses de 55 a 100% da DR e compatível na dose de 40% da DR. A maioria dos carrapaticidas químicos avaliados não foi compatível com o fungo M. anisopliae; apenas aqueles formulados com cipermetrina e com spinosad mostraram alguma compatibilidade para serem empregados em uma possível estratégia de uso associado.
COMPATIBILITY OF METARHIZIUM ANISOPLIAE WITH CHEMICAL ACARICIDES
Keywords: Biological control; microbial control; entomopathogenic fungus; Riphicephalus (Boophilus); microplus; cattle tick; Controle biológico; controle microbiano; ungo entomopatogênico; Riphicephalus (Boophilus); microplus; carrapato de bovinos